Rada Szkolna Krajowa – geneza powstania i pierwszy rok działalności - Rauch, Małgorzata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Artykuł przedstawia genezę powołania 24 stycznia 1868 r. Rady Szkolnej Krajowej – nowego organu administracji szkolnej, któremu powierzono zadanie reformy oświaty w zaborze austriackim. Autor prezentuje także pierwszy rok działalności Rady, jej zmagania o zakres kompetencji i kształt przyszłego szkolnictwa budowanego na kanwie dążeń środowisk społecznych do niepodległości i odbudowywania polskości.

The article presents the genesis of the establishment of the National School Council on 24-th January 1868 – the new administrative authority which was entrusted with a task to lead educational reform during the Austrian partition. The author shows the first years of the Council’s activities, its struggles in the pursuit of creating a range of competences and forming the educational system based on social aspirations that were aimed at independence and rebuilding of Polishness.
The National School Council – the Genesis and the First Year of Activity
Keywords: Rada Szkolna Krajowa; kuratorium oświaty; nadzór oświatowy; the National School Council; the Office of Education; pedagogical supervision